Influence Digital Literacy on Students' Reading Interest with Consider Concentration Study Students in Social Sciences Lessons - Sarlin, Sarlin; Iskandar, Iskandar; Herlina, Herlina (PT. Riset Press International, 2024)
Education can do it too carried out through two things ie formal education. Formal education is education that can be obtained with follow activity or a structured educational program as well as planned by government agencies for example through school or university. Formulation problem is There is influence digital literacy towards interest read students, Is there is difference interest read between students who have concentration height and concentration low, Is There is influence interaction between digital literacy with concentration Study student to interest read student. Research purposes Prove exists influence interaction between digital literacy and concentration Study student to interest read student. Types of research This is experiment. According to Sugiyono (2022) method study quantitative is method research conducted​ with experiments used​ For know influence independent variable ( treatment ) towards variable dependent ( interest read ) in controlled conditions.​ On research experiment writer use One class the divided into two groups that is group experiments and groups control. Research result. Normality test done For know population studied​ normally distributed or No. And is condition for parametric tests, if significance > 0.05, then population normally distributed, if significance < 0.05 then population distribute not normal, because significance > 0.05 then decided population normal distribution.